A STUDY ON THE TECHNIQUES OF TEACHING ENGLISH TO THE FIFTH YEAR STUDENTS IN SDN CEPOKO 1 SUMBERLAWANG SRAGEN - PRIMASARI, PATRICIA NANDA (2011)
In this study, the writer describes the techniques of teaching English to the fifth year students in SDN Cepoko 1 Sumberlawang Sragen. The objective of the study is that the writer intends to describe the techniques in teaching English at SDN Cepoko 1 Sumberlawang Sragen, and the problems faced in the teaching and learning process. The writer does three ways in collecting the data, namely: observation, interview and document. The data are field notes that are taken from teachinglearning process, note of interview with the teacher about the techniques used and document to support teaching English. In collecting data, the writer focuses at the fifth year of SDN Cepoko 1 Sumberlawang Sragen. The writer found the techniques of teaching English to the fifth year students in SDN Cepoko 1 Sumberlawang Sragen, namely: pictures observation, antonyms, discussion and songs. The writer found the problems faced by the teacher, namely: having limited pronounciation of students, and managing class. Besides, the problems faced by the students are limited vocabulary, pronunciation, and the less confidence. The problem solving used by the teacher to overcome the problems faced by the teacher and the student, such as: the teacher gives motivation to the students in order to make them feel confident to be in front of class. The teacher uses techniques that make them not bored and always focus on material. The teacher uses techniques in order to make the students easier to understand the materials.